THE EFFECT OF VIDEO MEDIA EDUCATION ON STUDENTS KNOWLEDGE SCORES AT SMAN 1 JOGONALAN REGARDING TRADITIONAL MEDICINE IN HANDLING DYSMENORRHEA - Farah Nilasheli Basri; Nur Atikah; Rani Tiara Desty (Poltekkes Kemenkes Surakarta, 2026)
Dysmenorrhea is a common problem experienced by young women and can disrupt daily activities. Increasing knowledge about non-pharmacological management of dysmenorrhea can be achieved through educational animated videos. This study aims to determine the effect of educational video media on knowledge scores regarding the use of traditional herbal remedies for the management of dysmenorrhea at SMAN 1 Jogonalan. The respondents in this study are 68 female students in grade XI. This study used a pre-experimental one-group pretest–posttest design, with questionnaires distributed through Google Forms as the research instrument. Questionnaire validity testing was conducted using Pearson’s Product-Moment correlation test, which showed that 16 out of 26 questionnaire items were valid, with significance values ranging from 0.000 to 0.045, with a reliability of 0.770 (reliable), and the video media had a validity of 0.869. Data analysis was carried out using the Wilcoxon test to assess differences in knowledge scores before and after the provision of educational video media. The results of this study show an average pre-test score of 10.97 and an average post-test score of 12.47, resulting in a 1.5-point increase. A significant difference in students' knowledge between the pretest and the posttest, with a Sig. (2-tailed) value of 0.001 ≤ 0.05, indicating that video media influence students' knowledge of using traditional herbal remedies to treat dysmenorrhea. Based on these results, it can be concluded that video media as an educational support tool helps increase students' knowledge of the use of traditional herbal remedies for treating dysmenorrhea.